Lef1ΔN Binds β-Catenin and Increases Osteoblast Activity and Trabecular Bone Mass - Hoeppner, Luke H. (American Society for Biochemistry and Molecular Biology, 2011)
Lymphoid enhancer-binding factor (Lef) 1 is a high mobility group protein best known as a Wnt-responsive transcription factor that associates with β-catenin. Lef1ΔN is a short isoform of Lef1 that lacks the first 113 amino acids and a well characterized high affinity β-catenin binding domain present in the full-length protein. Both Lef1 isoforms bind DNA and regulate gene expression. We previously reported that Lef1 is expressed in proliferating osteoblasts and blocks osteocalcin expression. In contrast, Lef1ΔN is only detectable in the later stages of osteoblast differentiation and promotes osteogenesis in vitro. Here, we show that Lef1ΔN retains the ability to interact physically and functionally with β-catenin. Unlike what has been reported in T cells and colon cancer cell lines, Lef1ΔN activated gene transcription in the absence of exogenous β-catenin and cooperated with constitutively active β-catenin to stimulate gene transcription in mesenchymal and osteoblastic cells. Residues at the N terminus of Lef1ΔN were required for β-catenin binding and the expression of osteoblast differentiation genes. To determine the role of Lef1ΔN on bone formation in vivo, a Lef1ΔN transgene was expressed in committed osteoblasts using the 2.3-kb fragment of the type 1 collagen promoter. The Lef1ΔN transgenic mice had higher trabecular bone volume in the proximal tibias and L5 vertebrae. Histological analyses of tibial sections revealed no differences in osteoblast, osteoid, or osteoclast surface areas. However, bone formation and mineral apposition rates as well as osteocalcin levels were increased in Lef1ΔN transgenic mice. Together, our data indicate that Lef1ΔN binds β-catenin, stimulates Lef/Tcf reporter activity, and promotes terminal osteoblast differentiation.